CONTRADICTION OF TYPES OF FIGURATIVE LANGUAGE FOUND IN MATHEW CHAPTER 5 – 7 OF KUPANG MALAY, INDONESIAN, AND ENGLISH BIBLE: A CONTRASTIVE STUDY OF TRANSLATION PRODUCTS - Yandres Lao (Academic Journal of Educational Sciences, 2019)
This research entitled CONTRADICTION OF TYPES OF FIGURATIVE LANGUAGE FOUND IN MATHEW CHAPTER 5 – 7 OF KUPANG MALAY, INDONESIAN, AND ENGLISH BIBLE: A CONTRASTIVE STUDY OF TRANSLATION PRODUCTS This writing was aimed at figuring changes of figurative languages used in three different languages of Bible; Kupang Malay, Indonesian, and English. Data source of the research was figurative language in Mathew chapter 5 – 7. As a documentary research, the data was collected by reading and sorting types of figurative language. Analysis of the research applied typology and contrastive study. it was found that there are three different types of figurative language used in Kupang Malay, Indonesian, and English Bible. They are metaphor, simile, and paradox. Changes of figurative language are caused by each language’s characteristics.